Mahua literature in the discourse and dialectic of national literature - Tan, Kok Chin (2023)
Since the conception of the "Malaysian National Literature" in 1971, it has remained a focal point of cultural, political, and academic discussions. The discourse surrounding national literature not only addresses the legacy and innovation of culture but also encompasses the intricate relationships among ethnicity, language, and power. Against this backdrop, this study offers a profound exploration into the establishment, evolution, and controversies of Malaysia's national literature. The controversy over national literature stems from Malay scholars adopting a unitist perspective, advocating that literary works written in Malay should be regarded as national literature—a stance heavily influenced by Malay nationalism. Conversely, the Mahua (Chinese-Malaysian) literary community presents alternative perspectives. Taking the works of Fang Bei Fang, Chong Fah Hing and Ng Kim Chew as references, they each provide unique arguments concerning the definition and positioning of national literature. These arguments not only challenge traditional views but also lay the groundwork for contemplating a pluralistic construction of national literature. This research primarily seeks to analyze how Malay nationalism profoundly impacts the formation of national literature and to provide an in-depth reflection on biases arising from the centrality of language in national literary discourse. By meticulously studying and analyzing Malay and Mahua literature, the research examines their interactions, dialogues, and conflicts throughout various historical periods, aiming to unveil the commonalities between Mahua literature and national literature, and further exploring potentialities within a pluralistic framework. To create a comprehensive research framework, this study first adopts Kekes's theory of pluralism, emphasizing the diversity and inclusivity of literature. It then draws from Foucault's discourse theory, investigating the intertwined relationships among discourse, knowledge, and power. Lastly, the study incorporates the ecosystem concept by British ecologist Tansley, viewing literature as a vibrant, ever-evolving dynamic system. Our study underscores the profound influence of Malay nationalism in sculpting national literature. Approaching from the intervention of national institutions, this work reveals that national literature is essentially a product interwoven with discourse, power, and knowledge at various levels and and further highlights the biases present in Malay literature within the cultural realm. Notably, the linguistic biases present in constructing national literary discourse serve as a pivotal ideological reservoir for Mahua literature, enabling its contribution to the broader dialogue on pluralistic national literature. This amplifies the indispensable role of Mahua literature within the national literary landscape, providing fresh perspectives and theoretical paradigms for its nuanced understanding and evolution. In conclusion, the study asserts that the reassertion of Mahua literature's subjectivity is not only a historical necessity but also provides a solid foundation for its role in the pluralistic construction of national literature.